(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The research aimed to study the development of the cultivated area and production of anise crop in Syria during the period (2011-2021), and to evaluate the economic return of the crop production in Al-Ghab region based on the study of indicators of economic efficiency per dunum in the year )2022(. The research adopted the descriptive analytical approach in studying and estimating the equations of the general trend of the research variables during the period studied. The results of the time series analysis of the research variables showed that there was a general declining trend in the cultivated area and crop production at the country level during the studied period. The results of the evaluation of the economic return showed that the total costs of producing anise crop amounted to 2,240,076 SP / dunum, the net profit was 2,159,924 SP / dunum, the turnover time of the variable assets was 112.65 days, the profitability coefficient compared to production costs was 159.53%, and this means that every pound is invested as costs Production in the cultivation of the crop gives a profit of 159.53 pounds, which is a good indicator. The results also showed that the cultivation of anise has a good productive and economic efficiency, as the productive and economic efficiency index per dunum was 2.39 and 1.96, respectively.